2022
DOI: 10.1177/10760296221076148
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Variation and Associated Organizational Factors of Pregnancy-Related Venous Thromboembolism in China

Abstract: Objective Identifying organizational factors affecting venous thromboembolism (VTE) incidence and variations between hospitals. Methods From a 2019 survey of VTE and live births in 113 hospitals, organizational factors: (hospital type, characteristics, live birth number), resource availability: (D-dimer, B-scan ultrasonography of lower extremity veins, computed tomographic pulmonary angiography [CTPA], and competency: [risk assessment, use of anticoagulants and patient education], data were collected and the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…VTE in the female demographic manifests at a youthful age of 40 in 50% of cases, with 20% of these cases linked to pregnancy, as per data from the RIETE [ 3 ]. Survey findings suggest that the incidence of pregnancy-related VTE in China, the United Kingdom, and the United States is 0.068%, 0.107%, and 0.066%, respectively [ 4 6 ]. Currently, thrombosis and thromboembolism stand as the primary causes of maternal morbidity and mortality [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…VTE in the female demographic manifests at a youthful age of 40 in 50% of cases, with 20% of these cases linked to pregnancy, as per data from the RIETE [ 3 ]. Survey findings suggest that the incidence of pregnancy-related VTE in China, the United Kingdom, and the United States is 0.068%, 0.107%, and 0.066%, respectively [ 4 6 ]. Currently, thrombosis and thromboembolism stand as the primary causes of maternal morbidity and mortality [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the associations of specific periods of GWG with the category of VTE, PE, or DVT with or without PE have not been reported. In addition, few studies have examined trends in the incidence of pregnancy-related VTE in China, and these studies have shown variable results (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%